Respuesta :
Answer:
y- value of the vertex for the given function [tex]\:f\left(x\right)\:=\:-\left(x\:-\:3\right)\left(x\:+\:11\right)[/tex] is 49.
Step-by-step explanation:
Given : The function [tex]\:f\left(x\right)\:=\:-\left(x\:-\:3\right)\left(x\:+\:11\right)[/tex]
We have to find the y- value of the vertex for the given function.
Consider the given function [tex]\:f\left(x\right)\:=\:-\left(x\:-\:3\right)\left(x\:+\:11\right)[/tex]
The vertex of the up-down facing parabola of the form [tex]y=a\left(x-m\right)\left(x-n\right)[/tex] is the average of the zeros, [tex]x_v=\frac{m+n}{2}[/tex]
Thus, here, m = 3 , n = -11 and a = 1
[tex]x_v=\frac{3+\left(-11\right)}{2}=-4[/tex]
Thus, x- value of vertex is -4.
Now, put x = -4 to get y values
[tex]y_v=-\left(-4-3\right)\left(-4+11\right)=49[/tex]
Thus, y- value of the vertex for the given function [tex]\:f\left(x\right)\:=\:-\left(x\:-\:3\right)\left(x\:+\:11\right)[/tex] is 49.